2021
DOI: 10.3389/fphar.2021.638556
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Intravenous Vitamin C for Preventing The Disease Aggravation of Moderate COVID-19 Pneumonia. A Retrospective Propensity Matched Before-After Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic is continuing to impact multiple countries worldwide and effective treatment options are still being developed. In this study, we investigate the potential of high-dose intravenous vitamin C (HDIVC) in the prevention of moderate COVID-19 disease aggravation.Methods: In this retrospective before-after case-matched clinical study, we compare the outcome and clinical courses of patients with moderate COVID-19 patients who were treated with an HDIVC protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
(31 reference statements)
0
43
0
1
Order By: Relevance
“…To date, few studies have looked into the effectiveness of early treatment of patients with COVID-19 with vitamin C/ascorbic acid [ 22 ]. One study found that high-dose intravenous vitamin C provided a 72% improvement in symptoms and reduced recovery time [ 17 ]. In contrast, a study that used an oral combination of vitamin C and zinc did not find a significant difference in the improvement of symptoms between the treatment and the control group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few studies have looked into the effectiveness of early treatment of patients with COVID-19 with vitamin C/ascorbic acid [ 22 ]. One study found that high-dose intravenous vitamin C provided a 72% improvement in symptoms and reduced recovery time [ 17 ]. In contrast, a study that used an oral combination of vitamin C and zinc did not find a significant difference in the improvement of symptoms between the treatment and the control group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intravenous vitamin C (IVC) has known immune-stimulating and antiviral properties [14] and had shown promise as a treatment for acute respiratory syndrome and pneumonia [15]. Recent studies reported on the benefits of IVC therapy for COVID-19 [16,17]. Furthermore, a large number of studies (n > 200) have demonstrated low vitamin D levels to be a risk factor for the severity of COVID-19 symptoms and hospitalization [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observational studies with hospitalized COVID-19 patients who received high-dose intravenous vitamin C (HDIVC) also reported improvements in oxygen support status, reduced mortality [27], and improvements in the inflammatory response [28,29], and immune and coagulation function [28]. Different results were found by , in which intravenous vitamin C did not decrease the incidence of mortality, vasopressor requirements, sequential organ failure assessment score (SOFA score) or ventilator settings [30].…”
Section: Studies Addressing Vitamin C Supplementation During Covid-19mentioning
confidence: 99%
“…Additionally, compared to the control group, there was a shorter duration of systemic inflammatory response syndrome (SIRS, p = 0.0004) and lower SIRS occurrence (p = 0.0086) during the first week. It was concluded that in this population, a dose of 7 g for a 70-kg person may be of value in preventing progression from moderate to severe disease [39]. 8.…”
mentioning
confidence: 99%